Quantitative evaluation of normal cerebrospinal fluid flow in Sylvian aqueduct and perivascular spaces of middle cerebral artery and circle of Willis using 2D phase-contrast MRI imaging - Le, Rosemarie Faustina D.; Karmonik, Christof; Regnier-Golanov, Angelique S.; Golanov, Eugene V.; Britz, Gavin W. (Frontiers in Neuroscience, 2025)
IntroductionRecently, it was proposed that CSF flow comprises a critical part of the glymphatic system, playing a role in various brain abnormalities from Alzheimer’s disease to hydrocephalus. Thus, CSF flow measurements have been increasingly used for diagnostic and clinical monitoring purposes. However, CSF flow in the periarterial spaces of the circle of Willis and the middle cerebral artery remain unexplored.MethodsWe employed phase-contrast MRI to establish baseline parameters of CSF flow along the perivascular spaces of the circle of Willis and the middle cerebral artery and compare them with the Sylvian aqueduct. We also developed a new, semi-automated method for outlining the perivascular spaces and extracting CSF flow parameters. The 24 healthy participants were recruited to achieve an even distribution by age (mean: 40 ± 11) and gender (13 males, 11 females).ResultsFor most CSF flow parameters, the circle of Willis and middle cerebral artery were similar but differed from the Sylvian aqueduct. The linear mixed models and general linear mixed models for CSF flow parameters, except for time to peak velocity, indicated strong effects of the conduits. CSF velocity was lower by 0.159 cm/s in the circle of Willis and 0.198 cm/s in the middle cerebral artery than in the Sylvian aqueduct. Overall, differences in CSF flow parameters between sex and age groups were negligible.DiscussionOur semi-automated routine for CSF flow measurements in the Sylvian aqueduct (0.00700 mL/s) aligned with the range of literature values, 0.0049–0.0432 mL/s. In this study, we have established baseline values of CSF flow along the circle of Willis and the middle cerebral artery as well as highlighted the limited influence of sex and/or age.